(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article is devoted to the definition of actual problems of professional training of music teachers. The author conducts a critical analysis of scientific research of various directions and determines ways to improve the training of future teachers-musicians. In the first direction, the implementation of modern approaches in teaching students – integrated, integrated and interactive - is considered.